Estrategias metodológicas que utilizan los docentes en el proceso de interaprendizaje, de la asignatura de matemática y su incidencia en el logro de aprendizajes significativos, por parte de los estudiantes de octavo año de educación básica, del colegio nacional nocturno mixto Manuel Enrique Rengel, de la Ciudad de Loja, período: 2008-2009, lineamientos alternativos”. - Gonzaga Ríos, Francisco Xavier (2009)
The following Doctorate thesis called: “ METHODOLOGICAL STRATEGIES USED BY MATH TEACHERS IN THE TEACHING- LEARNING PROCESS , AND THEIR INCIDENCE ON 8TH GRADERS TO GET A SIGNIFICANT LEARNING IN THE -NACIONAL NOCTURNO MIXTO MANUEL ENRIQUE RENGEL-SCHOOL, IN LOJA CITY. 2008-2009, ALTERNATIVE LINEAMENT”, collects results gotten along this research work through different: surveys , well structured interviews to authorities, Teachers, Students, Parents, and Supervisors who work for Manuel Enrique Rengel School, this supervisors have to do with teaching methodological strategies used by math teachers in 8th grade and their incidence on a meaningful students learning. I’ve done this investigation based on the Scientist Method, and its basis are focus on four different stages, such as: deduction, observation, proof and verification of results. The only purpose is to determine how real can be the investigated problem, besides that, this method can make generalizations with the results gotten from this research. Furthermore, the Hypothetic- Deductive- Inductive method, was applied , it helped me to observe all phenomenon and facts found along this investigative process. On the other hand, The Synthetic- Analytic method let me split this whole theme into small pieces, This allowed me obtain real and confident information. The descriptive method let me explore the theme previously mentioned, and I also could identify and describe this investigation based on epistemological and conceptual theoretical concepts, besides that, statistics techniques were used, were all results gotten in the research were showed through graphs to be analyzed and interpreted, which helped to emit final conclusions at the end. Among all the techniques used in this research I can mention : interviews, surveys, graphic representation, in addition I used the observation technique, and I also verified the object – subject of this matter along the whole investigative process. 84 people were taken as sample of the investigation and different investigative instruments were applied to them according to their specific work position or work function. The general objective proposed in this thesis has been formulated as it follows: “Determine how Math teachers apply their methodological strategies in their teaching - learning process on 8th grade students in the “ Nacional Nocturno Mixto Manuel Enrique Rengel” School, in Loja city , 2008-2009 and their incidence to get a significant learning on students. From the results gotten in this investigative work , I can conclude that in the Nacional Nocturno Mixto Manuel Enrique Rengel School, Teachers and Students don’t know about methodological strategies to teach Math, consequently there can’t be a meaningful learning , a traditional process of teaching is immerse in the teaching process , which becomes an obstacle to empower a better teaching process. Results already gotten let me expound an “alternative proposal” to face this serious problem, Through workshops or seminars based on the use and management of the progressive methodological strategies in order to get a high- quality learning, and to empower a real meaningful learning process on students, This alternative could help better students and teachers to face daily life situation.